2004
DOI: 10.1021/la049394o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Titania-Supported Platinum Catalyst:  The Effect of pH on Morphology Control and Valence State during Photodeposition

Abstract: Solid-supported metal catalysts have been widely used in industrial processes. The morphology of coated metal on the support is usually an important factor affecting the efficiency of the catalyst. In this study, a photocatalytic process is utilized to control the morphology of platinum particles deposited on titania (Degussa P-25). More specifically, the effect of pH on the morphology and the valence state of platinum nanoparticles was systemically investigated. It is found that, via a simple pH-controlled pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 52 publications
4
80
0
1
Order By: Relevance
“…The surface composition of the Pt NPs in the various catalysts treated in TEOA does not differ much. All NPs contain metallic Pt 0 besides oxidized Pt 2+ , reflected by Pt 4f 7/2 peaks at 70-72 eV and 74 eV, respectively [19] (Figure 3c). Especially in the AIS-containing samples, these peaks are very broad, making a meaningful deconvolution into distinct doublets for 4f 7/2 and 4f 5/2 difficult.…”
Section: Characterization Of As-prepared and Used Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface composition of the Pt NPs in the various catalysts treated in TEOA does not differ much. All NPs contain metallic Pt 0 besides oxidized Pt 2+ , reflected by Pt 4f 7/2 peaks at 70-72 eV and 74 eV, respectively [19] (Figure 3c). Especially in the AIS-containing samples, these peaks are very broad, making a meaningful deconvolution into distinct doublets for 4f 7/2 and 4f 5/2 difficult.…”
Section: Characterization Of As-prepared and Used Catalystsmentioning
confidence: 99%
“…This is probably due to the fact that not the whole amount of the solved [PtCl 6 ] 2− precursor but only a part of it is reduced and deposited as Pt NPs in basic TEOA solution. It has been shown that at high pH (as in the presence of TEOA) a stepwise hydrolysis occurs according to [PtCl 6 ] 2− → [Pt(OH) x Cl 6−x ] 2− → [Pt(OH) 6 ] 2− which hampers the formation of metallic Pt particles [19]. Moreover, the rather non-polar surface of CN might be less prone than the polar AIS surface to adsorb the polar Pt complex species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTAB probably forms micellar species since its concentration in solution (around 5 mM in the final solution) is higher than the Critical Micellar Concentration (0.8-1.1 mM) [37]. When the aged H 2 PtCl 6 solution is added, the Pt 4+ cation could be surrounded by different coordination shells since the ageing of the solution is supposed to lead to the partial or complete substitution of chloride ligands by hydroxides ones [21,22,38]: (1), an interaction between CTAB and the platinate salt could be envisaged. Such an interaction could lead to {Pt 4+ -CTAB} moieties as it was previously demonstrated for palladium [14].…”
Section: Proposition Of a Mechanism For Platinum Nanoparticles Formationmentioning
confidence: 99%
“…Materials based on titanium dioxide are well known for the pronounced catalytic and photocatalytic properties [1][2][3][4][5][6][7] . Presence of metallic nanoparticles formed of platinum group metals in oxide systems based on titanium dioxide, often leads to increased catalytic activity [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%